Scholarly communication offices as informative spaces in interection with univeristy libraries: Scope of action and offered services - Silva, Eduardo Graziosi [UNESP]; Rego-Piva, Laura Maria [UNESP]; Guimarães, José Augusto Chaves [UNESP] (Ibersid, 2021)
Considering the challenges that are presented to university libraries these days, to also guide users-researchers on issues related to scientific communication, the menus of the websites of scholarly communication offices of nine universities that appear in leading positions in the four most important international university rankings (ARWU, THE, QS, and Leiden) are analyzed in terms of characterization and of services and products offered according to the González-Solar's proposal (2016). The results show a strong predominance of support services for scientific publication and increased visibility, as well as guide services for open access publication. This scenario can serve as an action model for university libraries to take charge of the demands of scientific communication, always bearing in mind that the planning of products and services must consider the institutional needs and the strategic planning of the university in a way that reflects the needs of researchers.
Os escritórios de comunicação científica como espaços informacionais em interação com as bibliotecas universitárias: Âmbito de atuação e serviços oferecidos
Keywords: Evaluation of services; Scholarly communication offices; University libraries